Effect of lime concentration on gelatinized maize starch dispersions properties. (1st April 2015) - Lobato-Calleros, C.; Hernandez-Jaimes, C.; Chavez-Esquivel, G.; Meraz, M.; Sosa, E.; Lara, V.H.; Alvarez-Ramirez, J.; Vernon-Carter, E.J.
Highlights: The effect of lime concentration on gelatinized maize starch gels was studied. XRD, FTIR showed that crystallinity decreased at lime concentrations <0.20% w/w. Viscoelastic moduli decreased with increasing lime concentrations. Electrical properties showed an optimal lime concentration range (0.20–0.25% w/w). Abstract: Maize starch was lime-cooked at 92 °C with 0.0–0.40% w/w Ca(OH)2 . Optical micrographs showed that lime disrupted the integrity of insoluble remnants (ghosts) and increased the degree of syneresis of the gelatinized starch dispersions (GSD). The particle size distribution was monomodal, shifting to smaller sizes and narrower distributions with increasing lime concentration. X-ray patterns and FTIR spectra showed that crystallinity decreased to a minimum at lime concentration of 0.20% w/w. Lime-treated GSD exhibited thixotropic and viscoelastic behaviour. In the linear viscoelastic region the storage modulus was higher than the loss modulus, but a crossover between these moduli occurred in the non-linear viscoelastic region. The viscoelastic properties decreased with increased lime concentration. The electrochemical properties suggested that the amylopectin-rich remnants and the released amylose contained in the continuous matrix was firstly attacked by calcium ions at low lime levels (<0.20% w/w), disrupting the starch gel microstructure.